Postharvest grey mould development was suppressed by Origanum dictamnus oil vapours in tomato, pepper and eggplant fruit - Stavropoulou, Andriana; Chrysargyris, Antonios; Goumas, Dimitrios E.; Magan, Naresh; Loulakakis, Konstantinos A.; Tzortzakis, Nikos G. (My University, 2021)
Worldwide, significant postharvest losses of fruit and vegetables due to attack by microorganisms is evidence, while chemical applications is of great consumer concerns regarding food safety. Alternative sanitizers are explored, with natural compounds such as essential oils (EOs) to achieve scientific and consumer's interest for the preservation of fresh produce. In the present study, the efficacy of dittany (Origanum dictamnus L.) essential oil for the control of Botrytis cinerea, a common postharvest pathogen of three economically important vegetables, tomato, pepper and eggplant was examined. Pathogen development (vegetative or reproductive phase) in culture medium or in fruits was evaluated after treatment with dittany EO (0, 50, 100, 250 μL L-1) in vitro and in situ when stored at 12°C and 95% RH during or following exposure to EO volatiles. In vitro, fungal development was completely inhibited by the application of 100 or 250 μL L-1 of EO volatiles. In inoculated fruits, the application of 50 μL L-1 EO resulted in suppressed disease development by reduced lesion growth and fungal sporulation, where increasing EO concentration led to greater effects. Pre-exposure of the three fruits to volatiles, before fungal inoculation, revealed reduced lesion growth, indicating that dittany EO probably caused induced resistance of fruits against the pathogen. Moreover, EO application did not affect quality-related characteristics of fruits in general, while skin lightness and pulp lightness of eggplant fruits were improved under the presence of dittany EO volatiles. Overall, the results suggest that dittany EO volatiles may be considered as an alternative food preservative treatment, significantly reducing or eliminating B. cinerea infection during fruit storage.
Keywords: Botrytis cinerea; Essential oil; Fungal growth; Vegetables